The Economic Impact of Expanding Access to Finance in Mexico - Bruhn, Miriam (World Bank, Washington, DC, 2012)
The ninth in series of impact notes examines the impact of a large-scale banking expansion in Mexico, showing that simply increasing access to finance can have important economic effects.